Differential diagnosis algorithm of endogenous catatonia, catatonia-morphic and catatonia-mimicking states - D. N. Safonov (Zaporozhye State Medical University, 2017)
Subject relevance. The process of mental pathology pathomorphosis leads to the polymorphism of its clinical manifestations and, as a consequence - to difficulties in identification and differential diagnosis. The solution to this problem is in the adaption of diagnostic methodology to clinical realities by including into their structure instruments formed basing on pathomorphosis factors and trends. In this perspective, the most prominent example is endogenous catatonia, which in the academic tradition is conventionally affiliated with the form of schizophrenia with the same name. According to the classical understanding, endogenous catatonia, or, in the narrow sense - catatonic syndrome, is a group of intermittent motor disorders, arranged with polymorphic shell constellation of neuropsychiatric manifestations. The aim is to develop pathomorphosis adapted clinical algorithm of endogenous catatonia differential diagnostics. Materials and methods: 236 patients of Zaporizhzhia Regional Psychiatric Clinic were examined. Patients were divided into groups due to their mental disorders: - core group: patients with elements of endogenous catatonia in the structure of different clinical forms of schizophrenia (there were 144 patients in this group); - comparison group #1: 69 patients with late neurotropic effects of neuroleptic therapy (LNENT); - comparison group #2: 103 patients with catatonia-morphic dissociative disorders (CDD); - comparison group #3: 90 patients with organic catatonic disorder (OrCD); Results. Using Bush-Francis Catatonia Rating scale as an instrument of clinical analysis and statistical research of results with A. Wald's sequential analysis (modificated by E. V. Gubler) an algorithm of differential diagnostics of endogenus catatonia which includes 3 steps of Recognition Scale for Endogenous Catatonia is developed. Conclusion. Designed scales have a number of categorical differences from existing analogues, foremost by virtue of specificity of clinical-discursion compositions of using marks and disqualified conditions and excluding phenomena spectrum availability. The validity level: true positive diagnostic results (sensibility) = 94.43 %, pseudo-negative = 5.56 %, true negative (specificity) = 90.00 %, pseudo-positive = 10.00 %.